2005
DOI: 10.1017/s0950268805005224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and predictors for mortality in patients with infective endocarditis at a university hospital in Taiwan from 1995 to 2003

Abstract: The clinical features and microbiological characteristics of 315 patients with definite or possible infective endocarditis (IE) from January 1995 to December 2003 were evaluated. There were 187 males and 128 females with a mean age of 51 years (range, 1 month to 92 years). Ninety-three patients (30%) had a diagnosis of valvular heart disease and 24 (8%) had received prosthetic valve replacement. Blood culture was negative in 62 patients (20%). Staphylococci (91 patients, 32%), including methicillin-susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In fact, although renal abnormalities in patients with IE have been reported to be common (22,23), there is little research into the relationship between renal dysfunction and prognosis. Several reports have suggested that patients with serum Cr levels greater than 1.5 or 2.0 mg/dL are at high risk for in-hospital mortality (6,7). Although these results may be consistent with the findings of the present analysis, few reports have so far undertaken any detailed examinations of the threshold and predictive abilities, such as the sensitivity and specificity of renal functional parameters, for IE-related death.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, although renal abnormalities in patients with IE have been reported to be common (22,23), there is little research into the relationship between renal dysfunction and prognosis. Several reports have suggested that patients with serum Cr levels greater than 1.5 or 2.0 mg/dL are at high risk for in-hospital mortality (6,7). Although these results may be consistent with the findings of the present analysis, few reports have so far undertaken any detailed examinations of the threshold and predictive abilities, such as the sensitivity and specificity of renal functional parameters, for IE-related death.…”
Section: Discussionsupporting
confidence: 90%
“…Several clinical parameters have been reported to be associated with increased mortality in patients with IE. White blood cell (WBC) numbers (3), renal failure (5-7), a bicuspid aortic valve (8), staphylococci infection (9,10) and diabetes mellitus complications (7,11) have been reported to be related with mortality in patients with IE. However, it is unclear how these prognostic indicators of IE change with transitions in the clinical features of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal distribution also showed the occurrence of IE with RHD was less than the other two underlying heart diseases in the period of 2007–2011. Some other data from tertiary care settings in Beijing, Hongkong and Taiwan recruiting IE cases during 1995–2007 display a similar declining trend in the proportion of RHD accompanied by rising of CHD and DVD. This change parallels the declining incidence of RHD in China over recent years, especially in urban areas.…”
Section: Discussionmentioning
confidence: 63%
“…Some report Staphylococci [19-21], others found Streptococci [4,5,23] to be most common pathogens. None of these studies included the underlying risk factors for the new classification of IE.…”
Section: Discussionmentioning
confidence: 99%